Quetiapine and Buspirone Both Elevate Cortical Levels of Noradrenaline and Dopamine In vivo, but Do Not have Synergistic Effects - Silverstone, Peter H.; Lalies, Maggie D.; Hudson, Alan (Frontiers in Psychiatry, 2012)
Decreased cognitive ability is a significant problem in schizophrenia, and it has been proposed that augmentation of antipsychotics with 5HT1A receptor agonists may improve cognitive performance. Clinical studies have been mixed but there have been no studies specifically examining the effects of combining the atypical antipsychotic quetiapine with the 5HT1A receptor partial agonist, buspirone on monoamine release. This is of interest given previous evidence that monoamine release can alter cognition in schizophrenia. In the present study we measured in vivo levels of monoamines in the frontal cortex of Sprague-Dawley rats and examined if buspirone (2.5mg/kg i.p.), altered monoamine release both when given alone and when combined with quetiapine (10mg/kg i.p.). We found that serotonin levels were not altered by either drug, either alone or in combination. In contrast, both buspirone and quetiapine monotherapy significantly increased release of noradrenaline (112% and 160% respectively) and dopamine (169% and 191% respectively) compared to controls. However, there were no additional increases in in vivo monoamine release when the combination of these drugs were given. One possible explanation for these negative findings could be that the intrinsic 5HT1A agonist activity of quetiapine on its own is of such significance that it isn’t further enhanced by buspirone. These findings do not support clinical studies combining buspirone and quetiapine, if these were to be used on the basis of enhanced monoamine neurotransmission. These findings may also have implications for the atypical antipsychotic drugs in development which combine dopamine D2 antagonism with 5HT1A partial agonism.